THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS TO IMPROVE STUDENTS’ SPEAKING ABILITY - Asri Setia Gusminar; Eva Devi Sofyawati (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
The use of Authentic Materials method in teaching descriptive text was chosen as a means to improve an active situation in their speaking ability. This research aimed to analyze the use of Autyhentic Materials method in descriptive text type to improve students’ speaking skill. This is a quantitative research using pre-experimental approach. 40 students from first grade students of SMAN 10 Garut were selected to be the respondents of this study. The data were obtained through oral test, and the time to do the research is about one month. Then, they were analyzed and reported descriptively. The finding revealed that the TPR was significantly effective in improving students’ speaking skill. The data from pre-test and post-test showed that the average of the students’ achievement in pre-test was 45.87 and the average of students’ achievement in post-test was 61.80 and the result of Liliefors test showed that tcritical = 2.145 ≤ tobserved = 9.394.The results of the test showed that the students can significantly improve their speaking skill after using Authentic Materials method in learning descriptive text. Based on the result of study, it can be concluded that the majority of students were interested in learning English speaking through Authentic Materials method in learning descriptive text. This result indicates that teaching descriptive text by using Authentic Materials method can make the students tend to be more active in the teaching and learning process.